2022
DOI: 10.3390/jof8080783
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol Boosts the Antifungal Effect of Fluconazole and Modulates Resistance in Candida auris through Regulation of the CDR1 and ERG11 Genes

Abstract: Candida auris is considered a serious fungal pathogen frequently exhibiting a high resistance to a wide range of antifungals. In this study, a combination of the quorum-sensing molecule farnesol (FAR) and fluconazole (FLU) was tested on FLU-resistant C. auris isolates (C. auris S and C. auris R) compared to the susceptible C. auris H261. The aim was to assess the possible synergy between FAR and FLU, by reducing the FLU minimal inhibitory concentration, and to determine the mechanism underlying the conjunct ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…Under physiological conditions, farnesol inhibits the yeast-to-hyphae transition, while tyrosol has the opposite effect in terms of morphogenesis (13,14). The observed potent inhibitory effect of these molecules at supraphysiological concentrations suggests that either farnesol or tyrosol may be a potential part of novel innovative preventive strategies against Candida biofilms, including against the C. auris sessile community as published previously (15)(16)(17)(18)(19). These studies showed that both molecules have a remarkable antifungal effect, interfering with redox homeostasis, virulence, and intracellular microelement contents against planktonic forms of C. auris; however, the transcriptome-based biofilm related changes remained to be elucidated (17,18,20).…”
Section: Introductionmentioning
confidence: 78%
“…Under physiological conditions, farnesol inhibits the yeast-to-hyphae transition, while tyrosol has the opposite effect in terms of morphogenesis (13,14). The observed potent inhibitory effect of these molecules at supraphysiological concentrations suggests that either farnesol or tyrosol may be a potential part of novel innovative preventive strategies against Candida biofilms, including against the C. auris sessile community as published previously (15)(16)(17)(18)(19). These studies showed that both molecules have a remarkable antifungal effect, interfering with redox homeostasis, virulence, and intracellular microelement contents against planktonic forms of C. auris; however, the transcriptome-based biofilm related changes remained to be elucidated (17,18,20).…”
Section: Introductionmentioning
confidence: 78%
“…Emerging antifungal compounds being investigated include natural compounds, antimicrobial peptides, immunotherapy, metals and nano particles, photodynamic and combinational therapy, and repurposed drugs [ 118 , 125 , 126 •, 127 ]. Colistin showed synergistic activity with amphotericin B against C. auris [ 128 ], while farnesol boosted the antifungal effect of fluconazole [ 129 ]. Fluconazole-resistant C. auris isolates have higher levels of chitin in their cell wall and increased susceptibility to a glucosamine-6-phosphate synthase inhibitor [ 130 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Several non‐antifungal agents that demonstrated synergy with azoles against C. auris isolates are listed in Table 2, but, their specific synergistic mechanism, has yet to be discovered. Farnesol, a quorum‐sensing molecule, enhances the efficacy of fluconazole against C. auris by inhibiting the activity of CDR1 , and downregulating ERG11 [132]. Similarly, another study demonstrated that farnesol modulates C. albicans susceptibility to amphotericin B [133].…”
Section: Combination Therapies To Enhance Azole Efficacymentioning
confidence: 99%